Teaching Western American literature - Harrison, Brady, 1963-; Tanglen, Randi Lynn (University of Nebraska Press, 2020)
"'Teaching Western American Literature' gives instructors a glimpse into the classrooms, syllabi, and assignments of leading scholars in the field"-- Provided by publisher.
Keywords: Western stories -- Study and teaching.; American literature -- Study and teaching.; West (U.S.) -- In literature -- Study and teaching.; Littérature américaine -- Étude et enseignement.; États-Unis (Ouest) -- Dans la littérature -- Étude et enseignement.; LITERARY CRITICISM / American / General; American literature -- Study and teaching; West United States